Nonalcoholic fatty liver disease in patients with type 2 diabetes mellitus and its association with cardiovascular disease. Issue 4 (July 2018) - Vanjiappan, Sivabal; Hamide, Abdoul; Ananthakrishnan, Ramesh; Periyasamy, Senthilkumar Gandhipuram; Mehalingam, Vadivelan
Abstract: Introduction: Non-alcoholic fatty liver disease (NAFLD) encompasses a wide spectrum of liver disease that ranges from hepatic steatosis to non-alcoholic steatohepatitis. Obesity and diabetes mellitus are the prime risk factors for NAFLD. The aim of this study was to find out the prevalence of NAFLD among patients with type 2 diabetes mellitus and to detect the association of NAFLD with cardiovascular disease in them. Study design: Prospective observational study. Material and methods: The study was conducted on 300 patients with type 2 diabetes mellitus attending the outpatient department of a tertiary care teaching hospital. All patients underwent hepatic ultrasonography to look for hepatic steatosis. Among the 300 patients, 124 were divided into NAFLD and non-NAFLD groups based on the ultrasound findings. These patients were subjected to electrocardiogram, 2D echocardiogram, carotid intima media thickness (CIMT) measurement and ankle brachial pressure index measurement along with measurement of markers of oxidative stress. Results: Hepatic steatosis was present in 61% of diabetic patients in this study. Cardiovascular disease was not found to be significantly associated in diabetic patients with NAFLD. However, cardiovascular risk factors like CIMT, high sensitivity c-reactive protein (hs-CRP) and malondialdehyde (MDA) were elevated in these patients. hs-CRP and MDA levels were found to be significantly associated with the severity of NAFLD. Conclusion: There is a high prevalence of NAFLD in type 2 diabetic patients. No correlation was detected between the presence of NAFLD and cardiovascular disease in them; although there was an association between cardiovascular risk factors and NAFLD.